Gist: A Review (Journal of Surgical Sciences, 2019)
Non-epithelial tumours of stomach and intestine were described and termed as leomyomas because they possessed smooth muscle features when examined under light microscopy.Recently cell of origin of these tumourshave been identified as a pluripotential mesenchymal stem cell programmed to differentiate into the interstitial cells of Cajal. Gastrointestinal stromal tumours (GIST) is widely accepted term used for these tumours.GISTs are not infrequent and can occur in any part of GI Tract and also may be extraintestinal in origin. Introduction of lmatinib, a Tyrosine Kinase Inhibitor [TKI] for treatment of GIST has made a great impact in the management options of these tumours which were refractory to majority of available cytotoxic drugs. High response rate to imatinib generated new research for newer drugs on one hand and defining genetic structure and changes in other tumours to develop more pecific and successful therapy.This review is an effort to consolidate present understanding and information about pathology diagnosis and management of GIST.Journal of Surgical Sciences (2012) Vol. 16 (2) : 86-97